Phenological patterns of herbaceous Mediterranean plant communities in spring: is there a difference between native and formerly-cultivated grasslands? - Hess, Manon C. M.; Gómez-Ruiz, Pilar Angélica; Morellato, Leonor Patrícia Cerdeira [UNESP]; Buisson, Elise (Agentschap Plantentuin Meise, 2022)
Background and aims – Plant phenology, defined as the timing of recurring life events like leaf flushing, flowering, or fruiting, is highly sensitive to environmental factors such as photoperiod, temperature, and moisture. Phenological synchrony between interacting species – such as plants and their pollinators – is of major importance to the structure and functioning of ecosystems. Plant phenology might also be affected by changes in edaphic conditions. However, whether former agricultural activities may shift phenological patterns of plant communities remains poorly understood. In this study, we evaluated the impact of past agricultural practices on herbaceous plant community phenology in the protected Mediterranean xeric grassland of La Crau (France). Material and methods – We compared (1) species composition, and (2) phenological patterns of annuals, perennials, Bromus rubens (annual), and Lobularia maritima (perennial), in formerly-cultivated plots – abandoned for 30 years – and intact native grassland plots (steppe), both subjected to itinerant sheep grazing. Key results and conclusion – Our results suggest that former agricultural activities can affect species composition of Mediterranean xeric grassland communities with differences visible after 30 years of abandonment, but only altered phenological patterns slightly. We suggest that climatic factors and sheep grazing acted as strong habitat filters constraining community assembly at the phenological level.
Keywords: agriculture legacy; Mediterranean dry grassland; phenological patterns; plant phenology; soil disturbance